Dynamic FEA analysis and optimization of a robotic arm for CT image guided procedures. (2018) - Roy, Ayan; Ghosh, Taniya; Mishra, Ruby; Shubham Kamlesh, Shah
Abstract: Cancer and tumour detection is a very essential diagnostic process. The procedure of biopsy with the help of robotic technologies to collect tissue sample is an expensive ordeal and available only in very high end hospitals. An effort was made to develop a robotic arm that will be cost effective in the procedure of biopsy. Prime objective of this research is to determine the structural accuracy of the robotic arm in long run. The virtual model of the robotic arm was designed in Solid Works 2016. Different views of the design are shown in this paper. An experimental model of the robotic arm was manufactured to check deviation in reaching a user defined target point. The design was subjected to finite element analysis in ANSYS 15.0. Study of the stress and strain analysis is done during its dynamic behaviour. Having attained the results of the analysis, further modifications are made in the model to obtain optimized deformation, stress and strain results. A net reduction in the maximum total deformation by 91.499% is achieved by making some required alteration. With these modifications, the accuracy of this robotic arm will be maintained for a longer period of time and provide better application in the medical field